Temporal changes in arbuscular mycorrhizal fungi communities and their driving factors in Xanthoceras sorbifolium plantations - Zhang, Yuexin; Ma, Yunxia; Ma, Xiuzhi; Li, Cuiwei (Frontiers in Microbiology, 2025)
Arbuscular mycorrhizal fungi (AMF) communities are influenced by soil nutrients and plant and litter traits during forest ecosystem development. However, the extent to which these factors influence AMF communities in Xanthoceras sorbifolium plantations is unclear. In this study, rhizosphere soil samples were collected from 5-, 13-, 24-, 35-, 47-, and 56-year-old X. sorbifolium plantations. The AMF community was analyzed using Illumina MiSeq sequencing, and AMF spores were isolated and identified by wet sieving. The results showed that X. sorbifolium can establish a symbiotic relationship with AMF at different forest ages. In total, 5,876 AMF amplicon sequence variant (ASVs) were obtained from the soil samples and classified into 1 phylum, 4 classes, 6 orders, 12 families, and 15 genera. Glomus was the dominant genus. In addition, the diversity of AMF communities increased and then decreased with the age of X. sorbifolium, with no significant changes observed between 35-, 47-, and 56-year-old plantations. AMF community variance was primarily determined by soil-specific factors, with soil pH and root C content being the most influential. The results revealed the factors that drive AMF communities during the development of X. sorbifolium and provide valuable information for future conservation and planting management.